Faktor yang Berhubungan dengan Perilaku Buang Air Besar Sembarangan pada Masyarakat di Desa Oelpuah Kecamatan Kupang Tengah - Filldact Umbu Lado; Marylin S. Junias; Mustakim Sahdan (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2024)
Open defecation is an unhealthy behavior of defecating in fields, forests, bushes and other open areas, which is allowed to spread to cause health problems. Open defecation is influenced by various factors such as knowledge, availability of facilities and infrastructure, and support from health workers. This study aims to determine the factors associated with open defecation behavior in the community in Oelpuah village, Kupang Tengah sub-district. This study is a quantitative study using an analytical survey method with a cross-sectional research design. The population in this study were all heads of families in Oelpuah Village with a sample size of 77 people obtained from the results of Lameshow formula calculation then taken using simple random sampling technique. Data collection was done by filling out a questionnaire, after which the data were analyzed using chi-square test. The results of statistical tests showed that there were three factors that had a significant relationship with open defecation behavior, namely knowledge (p-value = 0.004), attitude (p-value = 0.007), socio-economic (pvalue = 0.006) and support of health workers (0,001). The conclusion of this study is that knowledge, attitude, socio-economic and support of health workers factors are associated with open defecation behavior.